2020
DOI: 10.1111/jfpp.14425
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the cooking methods of stir‐fried beef by instrumental analysis

Abstract: The objective of this study was to optimize the cooking process of stir‐fried beef and investigate the release of taste compounds during cooking by instrumental analysis. The contents of taste compounds in stir‐fried beef were determined by high‐performance liquid chromatography. The optimum result was: beef 100 g stir‐fried 4.00 min with blending oil 25.00 g, sucrose 1.75 g and salt 2.00 g, the content of total umami components showed an increasing trend with the maximum value (2,580.32 µg/g) at 4.00 min cook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The results showed that spices were beneficial for the release of flavor amino acids and increased its equivalent umami concentration (EUC). The EUC (154.5 gMSG/100 g) of fried beef packaged with spices was significantly higher than that of normal packaged fried beef (124.3 gMSG/100 g) [6]. Spices had a strong flavor enhancement effect, which was closely related to the flavor components in the spices.…”
Section: Introductionmentioning
confidence: 88%
“…The results showed that spices were beneficial for the release of flavor amino acids and increased its equivalent umami concentration (EUC). The EUC (154.5 gMSG/100 g) of fried beef packaged with spices was significantly higher than that of normal packaged fried beef (124.3 gMSG/100 g) [6]. Spices had a strong flavor enhancement effect, which was closely related to the flavor components in the spices.…”
Section: Introductionmentioning
confidence: 88%
“…They found that the spice contributed greatly to flavor development. The content of glutamic acid and aspartic acid in stir-fried beef between spice-added and nonspiced groups was very significant (Duan, Wang, et al, 2020).…”
mentioning
confidence: 89%
“…The application of heat treatment during the preparation of meat is aimed at improving its sensory properties (Hassoun, Aït‐Kaddour, et al., 2020). However, applying inappropriate heat treatments to meat products could lead to undesirable sensory and chemical changes due to the loss of amino acids or the synthesis of toxic compounds, or compounds that employ negative effects on meat color, flavor, or texture (Duan et al., 2020; Hassoun, Aït‐Kaddour, et al., 2020; Hassoun, Ojha, et al., 2020; Trevisan et al., 2016).…”
Section: Meat Cookingmentioning
confidence: 99%